Evaluation the Impact of Digital Technology on Children’s Mental Health and Psychological Wellbeing - Haryanto, Sri; Jemmy, Jemmy; Rumbiak, Helmin; Batubara, Fitri Amaliyah; Apriyanti, Eka (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
In the digital era, children are increasingly exposed to electronic devices such as smartphones, tablets, and computers from a young age, impacting their play, learning, and social interactions. Concerns about the potential effects on children's mental health and well-being have grown, prompting research into the psychological factors influencing technology adoption and its implications. This study employs a cross-sectional survey design to explore the relationship between digital technology usage and children's mental health. Data collected from 500 children aged 8-18 years in City X includes demographics, digital technology usage patterns, and assessments using validated scales. The findings reveal significant correlations: prolonged digital technology use correlates with increased risks of anxiety (r = 0.35, p < 0.01), depression (r = 0.30, p < 0.01), and behavioral issues (r = 0.25, p < 0.05) among children. The study underscores the importance of balanced and monitored technology use to mitigate adverse impacts on children's well-being. Collaborative efforts involving parents, educators, and policymakers are crucial in guiding children's technology usage to optimize benefits while safeguarding mental health. Future research aims to further understand these dynamics and develop effective strategies for promoting healthy digital habits among children.